Which one is better for non-alcoholic fatty liver disease, the Roux-en-Y gastric bypass or one anastomosis gastric bypass? A paired liver biopsy report. (June 2020) - Keleidari, Behrouz; Mahmoudieh, Mohsen; Kafi, Soroush; Shahabi, Shahab; Sheikhbahaei, Erfan; Farahmand, Alimohammad; Mahdavian, Shirin
Abstract: Background: Liver complications are one of the predictable outcomes of chronic obesity and bariatric surgery is one of the best way of diminishing them. This study was designed to compare the Roux-en-Y gastric bypass (RYGB) and Mini-Gastric bypass/One Anastomosis gastric bypass (MGB/OAGB) on non-alcoholic fatty liver disease (NAFLD). Methods: In this prospective study, 76 patients were operated with the RYGB or MGB/OAGB from 2016 to 2018. The weight, liver enzymes and liver pathology reports were evaluated at the base line. We asked all of the patients to come for second liver sampling one year after the surgery. All of the data analyzed by SPSS software. Results: secondary biopsy was taken from 43.4% of the patients one year after the surgery. According to Brunt system classification, in the RYGB and MGB/OAGB groups, 12.5% and 52.9% of them had no NAFLD respectively and 87.5% and 41.2% of them had Grade 1 NAFLD respectively. One patient (5.9%) in the MGB/OAGB group had Grade II NAFLD. The improvement of NAFLD was significantly better after the MGB/OAGB surgery (P = 0.021). Conclusions: Both RYGB and MGB/OAGB methods have predictable beneficial effects on weight loss, however, MGB/OAGB can improve NAFLD better than RYGB in short-term follow-up. Highlights: Gastric bypass procedures make significant change in fat composition and NAFLD. Both gastric bypass procedures improved NAFLD. MGB/OAGB improved NAFLD better than RYGB.